Tense Logic And Tense And Aspect In English - Bryan, Bob (Kansas Working Papers in Linguistics, 1979)
Problems encountered in interpreting a standard tense logic with tense operators P and F as a model for natural language are discussed. A formal system is presented which eliminates some of these problems of interpretation.